Management of multiple threats achieves meaningful koala conservation outcomes. Issue 4 (12th March 2018) - Beyer, Hawthorne L.; de Villiers, Deidre; Loader, Jo; Robbins, Amy; Stigner, Madeleine; Forbes, Neil; Hanger, Jonathan
Abstract: Management actions designed to mitigate development or anthropogenic impacts on species of conservation concern are often implemented without quantifying the benefit to the species. It is often unclear what combinations and intensities of management actions are required to achieve meaningful conservation outcomes. We investigate whether disease and predator control can reverse population declines of koalas ( Phascolarctos cinereus ). Based on longitudinal monitoring of the epidemiological and demographic status of over 500 animals over 4 years, coupled with an intensive disease and predator management programme, we use survival analyses to estimate annual age‐specific survival rates and population growth, and simulations to quantify the benefit of these actions. Predation and disease accounted for 63% and 29% of mortality, respectively, across all years, with wild dog (dingoes or dingo‐hybrids: Canis dingo, C. dingo × Canis familiaris ), carpet pythons ( Morelia spilota ) and domestic dogs ( C. familiaris ) accounting for 82%, 14% and 4% of confirmed predation mortalities, respectively. In the first 2 years, before disease and dog control had major impact, the population was declining rapidly with annual growth rates of 0.66 and 0.90. In the third and fourth years, after interventions had been fully implemented, the population growth rate had increased to 1.08 and 1.20. The intrinsic survival rate of joeys was 71.2% (excluding deaths resulting from the death of the mother). Adult survival rates varied as a function of sex, age and year. Even in a declining koala population, management actions can achieve meaningful conservation outcomes (population growth rates greater than one). However, benefits may be short‐lived in the absence of longer term strategies to manage threats. This work also identifies wild dogs as a major threat to koalas, highlighting the need to better understand how wild dog impacts vary in space and time. Policy implications . Offsetting policy that addresses habitat loss alone may achieve little or no meaningful benefit to declining koalas populations. Management must address suites of threats affecting these populations and ensure that the cumulative effects of these actions achieve positive population growth rates.